2019
DOI: 10.1177/1468087419882817
|View full text |Cite
|
Sign up to set email alerts
|

Impact and observations of cylinder deactivation and reactivation in a downsized gasoline turbocharged direct injection engine

Abstract: Cylinder deactivation, sometimes referred to as variable displacement engine technology, is a method being employed in state-of-the-art reciprocating engines to improve fuel economy. The approach involves disabling the valve actuation of one or more cylinders to deactivate them, thus forcing the engine to operate at a higher specific load across the remaining cylinders to produce the torque demanded. Operating at such a point with an increased throttle opening reduces the engine’s pumping losses and hence redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…A schematic diagram of the engine test facility is given in Figure 4. A brief description of this is given below, and further details may be obtained from Parker et al 67 As shown in Figure 4, the engine is connected to a dynamometer to allow the engine speed to be controlled and maintained within 61 rpm. The fuel flow rate of this engine is measured using an AVL PD733S fuel balance at a frequency of 50 Hz.…”
Section: Experimental Setup and Data Collectionmentioning
confidence: 99%
“…A schematic diagram of the engine test facility is given in Figure 4. A brief description of this is given below, and further details may be obtained from Parker et al 67 As shown in Figure 4, the engine is connected to a dynamometer to allow the engine speed to be controlled and maintained within 61 rpm. The fuel flow rate of this engine is measured using an AVL PD733S fuel balance at a frequency of 50 Hz.…”
Section: Experimental Setup and Data Collectionmentioning
confidence: 99%
“…Lumsden et al [4] and Shaded et al [5] demonstrated that downsizing with direct injection allows decreasing the pumping losses and increasing the compression ratio, thus reducing fuel consumption by around 25%. Besides, other interesting strategies are being applied to gasoline engines to improve fuel economy, such as exhaust gas recirculation (EGR), variable valve timing [6], deactivation of cylinders [7], and water injection in the intake ports [8].…”
Section: Introductionmentioning
confidence: 99%
“… General Motors debuted this system in 1981.  It continues to evolve as automobile manufacturers introduce new technologies [8]. Cylinder deactivation, which is utilized by automakers to progress fuel efficiency and diminish emissions, is based on this.…”
Section: Introductionmentioning
confidence: 99%